Fitness through time in ciliate microcosms experiment - Staffan Jacob; Delphine Legrand; Alexis S Chaine; Dries Bonte; Nicolas Schtickzelle; Michèle Huet; Jean Clobert (PANGAEA, 2017)
Habitat choice favours local adaptation at the thermal niche margin. Growth rate = fitness estimation of cells from each patch through a quantification of increased optical density per hour from a small number of cells from each patch, fitted from population growth curves using gcfit function (grofit R-package) with spline fit. Gene_flow_level = level of dispersal toward the focal population (10% or 30% of the local population extquotesingle initial carrying capacity). Time = time when growth rate measurements were performed, in weeks from the beginning of the experiment. Gene_flow_treatment = types of gene flow, with or without habitat choice.
In supplement to: Jacob, S et al. (2017): Gene flow favours local adaptation under habitat choice in ciliate microcosms. Nature Ecology & Evolution, 1(9), 1407-1410, https://doi.org/10.1038/s41559-017-0269-5